Measurements of the branching fractions of [lambda]+c→pπ−π+, [lambda]+c→pK−K+, and [lambda]+c→pπ−K+ - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Berninghoff, Daniel; Braun, Svende; Comerma-Montells, Albert; De Cian, Michel; Dziewiecki, Michal; Esen, Sevda; Gerick, David; Grabowski, Jascha; Grünberg, Oliver; et al. (Journal of high energy physics, 2018)
The ratios of the branching fractions of the decays Λ c + → pπ−π+, Λ c + → pK−K+, and Λ c + → pπ−K+ with respect to the Cabibbo-favoured Λ c + → pK−π+ decay are measured using proton-proton collision data collected with the LHCb experiment at a 7 TeV centre-of-mass energy and corresponding to an integrated luminosity of 1.0 fb−1: B(Λ+c→pπ−π+)B(Λ+c→pK−π+)=(7.44±0.08±0.18)%,B(Λ+c→pK−K+)B(Λ+c→pK−π+)=(1.70±0.03±0.03)%B(Λ+c→pπ−K+)B(Λ+c→pK−π+)=(0.165±0.015±0.005)%,B(Λc+→pπ−π+)B(Λc+→pK−π+)=(7.44±0.08±0.18)%,B(Λc+→pK−K+)B(Λc+→pK−π+)=(1.70±0.03±0.03)%B(Λc+→pπ−K+)B(Λc+→pK−π+)=(0.165±0.015±0.005)%, \begin{array}{l}\frac{\mathrm{\mathcal{B}}\left({\varLambda}_c^{+}\to p{\pi}^{-}{\pi}^{+}\right)}{\mathrm{\mathcal{B}}\left({\varLambda}_c^{+}\to p{K}^{-}{\pi}^{+}\right)}=\left(7.44\pm 0.08\pm 0.18\right)\%,\hfill \\ {}\frac{\mathrm{\mathcal{B}}\left({\varLambda}_c^{+}\to p{K}^{-}{K}^{+}\right)}{\mathrm{\mathcal{B}}\left({\varLambda}_c^{+}\to p{K}^{-}{\pi}^{+}\right)}=\left(1.70\pm 0.03\pm 0.03\right)\%\hfill \\ {}\frac{\mathrm{\mathcal{B}}\left({\varLambda}_c^{+}\to p{\pi}^{-}{K}^{+}\right)}{\mathrm{\mathcal{B}}\left({\varLambda}_c^{+}\to p{K}^{-}{\pi}^{+}\right)}=\left(0.165\pm 0.015\pm 0.005\right)\%,\hfill \end{array} where the uncertainties are statistical and systematic, respectively. These results are the most precise measurements of these quantities to date. When multiplied by the world-average value for B(Λ+c→pK−π+)B(Λc+→pK−π+) \mathrm{\mathcal{B}}\left({\varLambda}_c^{+}\to p{K}^{-}{\pi}^{+}\right) , the corresponding branching fractions are B(Λ+c→pπ−π+)=(4.72±0.05±0.11±0.25)×10−3,B(Λ+c→pK−K+)=(1.08±0.02±0.02±0.06)×10−3,B(Λ+c→pπ−K+)=(1.04±0.09±0.03±0.05)×10−4,B(Λc+→pπ−π+)=(4.72±0.05±0.11±0.25)×10−3,B(Λc+→pK−K+)=(1.08±0.02±0.02±0.06)×10−3,B(Λc+→pπ−K+)=(1.04±0.09±0.03±0.05)×10−4, \begin{array}{l}\mathrm{\mathcal{B}}\left({\varLambda}_c^{+}\to p{\pi}^{-}{\pi}^{+}\right)=\left(4.72\pm 0.05\pm 0.11\pm 0.25\right)\times {10}^{-3},\hfill \\ {}\mathrm{\mathcal{B}}\left({\varLambda}_c^{+}\to p{K}^{-}{K}^{+}\right)=\left(1.08\pm 0.02\pm 0.02\pm 0.06\right)\times {10}^{-3},\hfill \\ {}\mathrm{\mathcal{B}}\left({\varLambda}_c^{+}\to p{\pi}^{-}{K}^{+}\right)=\left(1.04\pm 0.09\pm 0.03\pm 0.05\right)\times {10}^{-4},\hfill \end{array} where the final uncertainty is due to B(Λ+c→pK−π+)B(Λc+→pK−π+) \mathrm{\mathcal{B}}\left({\varLambda}_c^{+}\to p{K}^{-}{\pi}^{+}\right) . Open image in new window
Im Titel wird Lambda als griechischer Buchstabe dargestellt
Im Titel sind "+" und "c" untereinander geschrieben: "+" hochgestellt, "c" tiefgestellt
Im Titel sind "+" und "-" hochgestellt
The LHCb collaboration: R. Aaij, P. d'Argent, S. Bachmann, D.Berninghoff, S. Braun, A. Comerma-Montells, M. De Cian, M. Dziewiecki, S. Esen, D. Gerick, J.P Grabowski, X. Han, S. Hansmann-Menzemer, M. Kecke, B. Khanji, M. Kolpin, R. Kopecná, B. Leverington, J. Marks, D.S. Mitzel, S. Neubert, M. Neuner, T. Nikodem, A. Piucci, M. Stahl, S. Stemmle, J. van Tilburg, U. Uwer, A. Zhelezov [und weitere]
Gesehen am 22.05.2019